1984
DOI: 10.1111/j.1432-1033.1984.tb07923.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipoteichoic acid biosynthesis in membrane lipid metabolism of growing Staphylococcus aureus

Abstract: Pulse-chase experiments with [2-3H]glycerol and [ 14C]acetate revealed that in Staphylococcus aureus lipoteichoic acid biosynthesis plays a dominant role in membrane lipid metabolism. In the chase, 90 % of the glycerophosphate moiety of phosphatidylglycerol was incorporated into the polymer :Glycerophosphodiglucosyldiacylglycerol was shown to be an intermediate, confirming that the hydrophilic chain is polymerized on the final lipid anchor.Total phosphatidylglycerol served as the precursor pool and was estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
116
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 48 publications
5
116
0
Order By: Relevance
“…Pulse-labeling of staphylococci with [ 14 C]acetate revealed that the label appeared successively in glucosyl diacylglycerol (Glc-DAG), Glc 2 -DAG, and eventually LTA (25). Pulselabeling with [2-3 H]glycerol demonstrated incorporation into PG and glycolipid-anchored LTA (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulse-labeling of staphylococci with [ 14 C]acetate revealed that the label appeared successively in glucosyl diacylglycerol (Glc-DAG), Glc 2 -DAG, and eventually LTA (25). Pulselabeling with [2-3 H]glycerol demonstrated incorporation into PG and glycolipid-anchored LTA (25).…”
Section: Discussionmentioning
confidence: 99%
“…Pulselabeling with [2-3 H]glycerol demonstrated incorporation into PG and glycolipid-anchored LTA (25). Stepwise degradation of pulse-labeled LTA from the glycerol terminus with phosphodiesterase and phosphomonoesterase revealed that the polymer chain grew distal to the lipid anchor (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Based on the average diameter of a lipoteichoic acid micelle, a number of related molecular properties can be estimated by using the following additional information: (a) as the diacylglycerol anchor of the lipoteichoic acid is derived from diacylglycerol from membranelipid metabolism [6], the diameter of the lipid core region of the lipoteichoic acid micelle can be estimated to amount of approximately 5 nm (= 2 rL, Fig. 3); (b) since the fatty acid chains of the lipoteichoic acid were found in the molten conformation, the area occupied by the lipid anchor at a distance rL from the center of the micelle should be in the order of approximately 0.5 nm2 1261; (c) the average hydrophilic chain of the staphylococcal lipoteichoic acid comprises about 25 glycerophosphate units [6].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the average diameter of a lipoteichoic acid micelle, a number of related molecular properties can be estimated by using the following additional information: (a) as the diacylglycerol anchor of the lipoteichoic acid is derived from diacylglycerol from membranelipid metabolism [6], the diameter of the lipid core region of the lipoteichoic acid micelle can be estimated to amount of approximately 5 nm (= 2 rL, Fig. 3); (b) since the fatty acid chains of the lipoteichoic acid were found in the molten conformation, the area occupied by the lipid anchor at a distance rL from the center of the micelle should be in the order of approximately 0.5 nm2 1261; (c) the average hydrophilic chain of the staphylococcal lipoteichoic acid comprises about 25 glycerophosphate units [6]. From simple geometrical considerations the following conclusions can be drawn: (a) each micelle is on average made up by about 150 lipoteichoic acid molecules, (b) the surface area available for each hydrophobic lipoteichoic acid chain amounts to approximately 10 nm2 at the surface of the micelle, (c) the outer hydrophilic shell of the micelle is heavily hydrated (nearly 80% of the volume of the outer shell is occupied by water), and (d) the hydrophilic poly(g1ycerophosphate) chains of the lipoteichoic acid exist in a heavily coiled conformation (the length of a fully extended chain consisting of 25 subunits would be in the order of 17.5 nm as compared to the estimated 8.5 nm thickness of the hydrophilic shell of the lipoteichoic acid micelle).…”
Section: Resultsmentioning
confidence: 99%